Training on the Utilization of Waste Waste into Brickets as Alternative Energy in Wringinpitu Village - Novita Nur Synthiawati; Akeo Wahyudi; Silvina Nur Aini; Angga Wahyu Hidayah; Deni Prasetyo (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2022)
Wringinpitu Village is one of the furniture-producing villages located in the Mojowarno District, Jombang Regency, East Java Province. As an industrial village that produces furniture, of course there are products from the manufacturing process that are not used, namely wood sawdust (grajen). Grajen is a sawn waste that is not reprocessed by the community. In community service carried out by the implementing team, they offered a solution in the form of training in the processing of sawn wood waste which resulted in briquette products. Briquettes are one of the alternative fuels that are environmentally friendly, briquettes can usually be made from rice husks, coconut shells, corncobs and grajen. Which is in the making through the process of burning or writing which will later be mixed with starch or tapioca as an adhesive and then printed as desired which can later be sold by the public. Briquettes are environmentally friendly steel products, the difference between briquettes and other charcoals is that they have minimal smoke and are more durable.